2019
DOI: 10.3390/su11123473
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Features of Agroforestry Research Based on Bibliometric Analysis

Abstract: The world is faced with dual challenges to ensure food security for its large and still growing population and to mitigate climate change. It is necessary to develop more diversified and multifunction agricultural systems to address the challenges. Therefore, as a reasonable land use practice, agroforestry has become the hotspot in scientific research in recent decades. This study performed quantitative and qualitative analyses of agroforestry research published between 1990 and 2018 based on bibliometric meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Indeed, it is a suitable land management system to reduce gender inequalities related to natural resource access (Wekesa et al, 2018). In light of addressing the livelihood situations in developing countries, agroforestry also plays an important role in the livelihoods of poor people (Liu et al, 2019). Agroforestry is a pathway toward more resilient livelihoods for millions of African farmers whose livelihoods are threatened by climate change and land degradation (Mbow et al, 2014).…”
Section: Social Functionsmentioning
confidence: 99%
“…Indeed, it is a suitable land management system to reduce gender inequalities related to natural resource access (Wekesa et al, 2018). In light of addressing the livelihood situations in developing countries, agroforestry also plays an important role in the livelihoods of poor people (Liu et al, 2019). Agroforestry is a pathway toward more resilient livelihoods for millions of African farmers whose livelihoods are threatened by climate change and land degradation (Mbow et al, 2014).…”
Section: Social Functionsmentioning
confidence: 99%
“…There are many studies reviewing various aspects of intercropping, including yield stability [24][25][26], water and nutrient utilization [27][28][29][30][31], biodiversity [32][33][34][35][36][37][38][39], allelopathy [17,[40][41][42][43][44], agroforestry [29,[45][46][47][48][49][50][51], or species-dependent intercropping such as cereallegume or maize-based intercropping [7,31,52,53]. However, no study has investigated the overall research tends and features of intercropping.…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has investigated the overall research tends and features of intercropping. Previous studies [45][46][47][48]54,55] have shown that scientometrics is a powerful tool for quantitative and statistical demonstration of research trends and features of a certain topic. The objective of this study is to quantitatively analyze the growth and evolution of intercropping research based on the scientometric method based on the Web of Science database.…”
Section: Introductionmentioning
confidence: 99%
“…However, the uneven and relatively slow uptake of agroforestry in Central and Latin America (Dagang and Nair 2003;Frey et al 2012a;Somarriba et al 2012) suggests that not all farmers deem these systems to be a desirable land-use option (Do et al 2020). While the ecological advantages of agroforestry have been widely documented (e.g., Jose 2009), the socio-economic disadvantages that may constitute barriers to adoption have received less attention in the literature (Liu et al 2019;Montambault and Alavalapati 2005). More research to better understand the socio-economic aspects of agroforestry is therefore needed, to help identify conditions that may make agroforestry more attractive for farmers.…”
Section: Introductionmentioning
confidence: 99%